PENGARUH KEJELASAN SASARAN ANGGARAN, KARAKTER PERSONAL, DAN INFORMATION ASYMMETRY PADA SENJANGAN ANGGARAN - Cika Putri, Gusti Ayu Made; Asri Dwija Putri, I.G.A.M. (E-Jurnal Akuntansi; Vol 14 No 3 (2016), 2016)
The purpose of this study was to determine the effect of budget goal clarity, personal character, and information asymmetry on budgetary slack in the regional work units Gianyar regency. The research was conducted on 30 SKPD located in Gianyar comprised of 15 offices, 8 agencies and 7 district offices. The samples used were 90 employees by using purposive sampling method. Data was collected using a survey method. Data analysis technique used is multiple linear regression. Based on the analysis found that the budget goal clarity and personal character negatively affect budgetary slack, while the information asymmetry has positive influence on budgetary slack.
Keywords: budget, budget clarity, personal character, asymmetry